1994
DOI: 10.2166/wst.1994.0413
|View full text |Cite
|
Sign up to set email alerts
|

Use of constructed wetlands in water pollution control: historical development, present status, and future perspectives

Abstract: During the last two decades the multiple functions and values of wetlands have been recognized not only by the scientists and managers working with wetlands, but also by the public. The ability of wetlands to transform and store organic matter has been exploited in constructed wetlands. This paper summarizes the state-of-the-art of the uses of constructed wetlands in water pollution control by reviewing the basics of the technology, the historical development, and the performance expectations with focus on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
124
1
6

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(132 citation statements)
references
References 32 publications
1
124
1
6
Order By: Relevance
“…A high hydraulic loading of 0.04 m 3 /m 2 d was reported in the literature for the treatment of pig farm wastewater using combined vertical and horizontal flow reed bed system . It is well recognized that the hydraulic loading rate is one of the most important factors affecting the purification process; the value has been recommended in the range between 0.025-0.050 m 3 /m 2 d (Brix, 1994). Clearly, the hydraulic loading rate used in this study is higher by one order of magnitude than those reported.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…A high hydraulic loading of 0.04 m 3 /m 2 d was reported in the literature for the treatment of pig farm wastewater using combined vertical and horizontal flow reed bed system . It is well recognized that the hydraulic loading rate is one of the most important factors affecting the purification process; the value has been recommended in the range between 0.025-0.050 m 3 /m 2 d (Brix, 1994). Clearly, the hydraulic loading rate used in this study is higher by one order of magnitude than those reported.…”
Section: Discussionmentioning
confidence: 79%
“…It is reported that the recirculation of effluent can enhance pollutants-microorganisms interaction by allowing a longer retention time without significantly changing the operation of the beds. It is well known that reed bed technology works on the principle that biofilms attached onto the bed medium break down pollutants in wastewater passing through the bed (Brix, 1994). Reeds have the ability to transfer a certain amount of oxygen to their roots, stimulating microbial activities and enhancing the breaking down of pollutants (Brix, 1994;IWA, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It involves a series of physical, chemical and biological processes such as adsorption in the bed matrix, filtration, pollutant sedimentation, ion exchange, plant sorption and microbiological reactions (Brix, 1994). Results from this study do not show a complete picture for the complicated transformations of NH 4 -N. Nevertheless, this study provides useful information to identify the fate of soluble NH 4 -N removed in downflow reed bed systems, particularly regarding the initial adsorption and retaining of NH 4 -N inside the bed matrices.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrient diversion through constructed wetlands have become an important tool in developed countries for efficient management of wastewater during the last decade (Brix, 1994;Kadlec & Knight, 1994;Knight, Kadlec, & Reed, 1992). However, economic feasibility of such systems limits their application, especially in developing countries (Sun & Qu, 1998).…”
Section: Introductionmentioning
confidence: 99%